Juventude e mercado de trabalho no Brasil: formação e empregabilidade - Rodrigues, Thiago Machado (2017)
Nowadays, society has been suffering from recurring economic crises in many ways. In this scenario, countries are greatly affected by unemployment which, in turn, is one of the main features of the current capitalist economic system. Furthermore, innovations brought by new production and management models driven by the microelectronics and information technology revolution also foster the creation or reduction of jobs. Unemployment hits society as a whole, but the youth of today is one of its levels which are most affected. Currently, young people seek their insertion into the labor market without any experience and qualification in a scenario in which, according to data from surveys, 50% of employers require hands-on experience as a prerequisite for employment. Through a qualitative and exploratory approach, the present study aimed to identify different aspects involving young Brazilians’ particularities and the main factors involving their insertion into the current labor market. For such a purpose, the historical development of labor evolution and its interactions with the capitalist system have been addressed, as well as the major changes in employment relationships, through which labor projections as to the future of society and the impacts caused by new forms of production and information technology were discussed. Issues concerning the interaction of young people with education and the labor market in Brazil were also addressed. The present Brazilian youth population and quality of education provided to such individuals, as well as its scope, were also discussed. Through an extensive use of secondary data from main national social survey agencies, an analysis of the labor market in Brazil has been conducted by highlighting aspects that lead to youth unemployment. In conclusion, young Brazilians are not inserted in the labor market mainly on account of lack of experience, qualification and jobs